Prospects and challenges of social media marketing in Bangladesh: a case of Global Digital Mart Ltd. - Nion, Sajid Hasan (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.